Polszczyzna jako język drugi w szkole. Wymagania leksykalne komunikacyjnej i edukacyjnej odmiany języka - Seretny, Anna (Neofilolog, 2022)
In the recent years the number of migrant children in Polish schools has grown considerably. Many of them barely speak our language, most of them do not know it at all. Thanks to the state language support program most of the pupils within a year or two learn how to communicate in Polish. This ability however is often of little help during subject lessons due to immense differences between communicative and an academic language variety. The text presents the results of a preliminary study undertaken to prove that academic lexis makes on migrant children tremendous demands and to show that due to its specificity and quantity its teaching has to be both, explicit and well-organized. To achieve the research goal of the lexical material was excerpted from one of the history textbooks for primary school fourth graders and then subjected to detailed analysis which aimed at its structured organization. The paper ends with pedagogical implications: it presents some strategies for developing lexical competence of migrant pupils which can help them to meet the challenge and learn subject vocabulary more effectively.